2021
DOI: 10.1007/s00394-021-02734-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of dairy intake with all-cause, cancer, and cardiovascular disease mortality in Japanese adults: a 25-year population-based cohort

Abstract: Purpose The association between dairy intake and mortality remains uncertain, and evidence for the Japanese population is scarce. We aimed to investigate the association between dairy intake and all-cause, cancer, and cardiovascular disease (CVD) mortality in Japanese adults. Methods A total of 34,161 participants (16,565 men and 17,596 women) aged 40–64 years without a history of cancer, myocardial infarction, or stroke at baseline were included in the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 67 publications
0
20
0
Order By: Relevance
“…Moreover, in the study of Goldbohm et al (16) , yogurt consumption was inversely associated with all-cause mortality among men but not women. In terms of CVD mortality, yogurt consumption was not associated with a lower risk of CVD mortality in nine cohorts (13,14,(25)(26)(27)(28)47,49) . However, two studies (12,16) revealed that yogurt consumption was inversely related to deaths from CVD.…”
Section: Findings From the Systematic Reviewmentioning
confidence: 87%
See 3 more Smart Citations
“…Moreover, in the study of Goldbohm et al (16) , yogurt consumption was inversely associated with all-cause mortality among men but not women. In terms of CVD mortality, yogurt consumption was not associated with a lower risk of CVD mortality in nine cohorts (13,14,(25)(26)(27)(28)47,49) . However, two studies (12,16) revealed that yogurt consumption was inversely related to deaths from CVD.…”
Section: Findings From the Systematic Reviewmentioning
confidence: 87%
“…Lack of such an association was also observed in another meta-analysis of prospective cohort studies (51) . It should be noted that several large cohort studies (13,(25)(26)(27)(28) have been published since the release of previous metaanalysis (17) . This might explain the diverse findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Vegetables are an excellent source of vitamins, minerals, other phytochemicals, and micronutrients, and eating vegetables daily is important for good health and provides antioxidants and fiber. Studies show that, 5 people who eat five or more servings of vegetables a day are less likely to develop many diseases, including cancer and heart disease. There are different types of vegetable preparation methods across the world, and six techniques have been described by many scholars, 6 namely, sautéing, blanching, steaming, boiling, frying, and freezing.…”
Section: Introductionmentioning
confidence: 99%